Law and the Brain. - Zeki, Semir (Philosophical transactions of the Royal Society of London. Biological sciences., 2006)
The past 20 years have seen unparalleled advances in neurobiology, with findings from neuroscience being used to shed light on a range of human activities - many historically the province of those in the humanities and social sciences - aesthetics, emotion, consciousness, music. Applying this new knowledge to law seems a natural development - the making, considering, and enforcing of law of course rests on mental processes. However, where some of those activities canbe studied with a certain amount of academic detachment, what we discover about the brain has considerable implications for how w.